Analysis of Occupational Safety and Health (OSH) Cost Requirements in The Construction of Rubaru 1 Elementary School - Permana, Midi Agus; Witjaksana, Budi; Purnama, Jaka (Asian Journal of Social and Humanities, 2025)
This research addresses the critical issue of insufficient budget allocation for Occupational Safety and Health (OHS) systems in construction projects, specifically in the Rubaru 1 Elementary School building project in Sumenep District, Indonesia. The study explores how limited financial resources for safety measures, such as personal protective equipment (PPE), worker training, and health facilities, affect the implementation and effectiveness of OHS systems. The urgency of this research lies in the growing need to allocate adequate resources to OHS, as insufficient funding increases the risk of workplace accidents, delays project timelines, and raises costs. Previous studies, including Lestari et al. (2023) and Saragi & Sinaga (2021), have emphasized the positive impact of adequate OHS budgets on reducing accidents and improving productivity. However, a gap exists in research regarding the specific cost components required for effective OHS implementation, especially in relation to construction projects with limited budgets. This study fills this gap by analyzing the key cost components for OHS and their direct impact on worker safety and project performance. The findings will provide valuable insights for construction companies to optimize their OHS budgets and enhance safety measures. It also contributes to the development of industry standards and practices for OHS management in future construction projects.